Profesor Turun Padang Technology and innovation with the people of Batik - Amir, Abdul Razak (UMPSA, 2023)
ULU TEMBELING, 13 December 2023 – In an effort to improve the standard of life of the Orang Asal Batik community in Kampung Bengoi, Ulu Tembeling, Pahang, lecturer of the Faculty of Mechanical and Automotive Engineering Technology (FTKMA), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Associate Professor Ts. Dr. Amir Abdul Razak together with Muslim Care Malaysia Society (MCM) and Malaysian Green Technology and Climate Change Corporation (MGTC) held a Technology Literacy Programme with the community there.